Etching of polycrystalline diamond films by electron beam assisted plasma - Rocca, Jorge J., author; Nishimura, Kozo, author; Miyata, Koichi, author; Miyauchi, Sihigeaki, author; Kobashi, Koji, author; Materials Research Society, publisher (Colorado State University. Libraries, 1996)
Polycrystalline diamond films were processed in a direct current plasma produced by a self-focused electron beam using combinations of H2, O2, and He as the processing gas. The film surfaces were observed by scanning electron microscopy, and characterized by x-ray photoelectron spectroscopy. It was found that for the case in which O2 was included in the processing gas, a high density of etch pits appeared on (100) faces of diamond grains, and oxygen was either physisorbed or chemisorbed at the film surface. It was demonstrated that the etching apparatus used was capable of forming at least a 5-μm wide pattern of polycrystalline diamond film.